BUDDHIST LAW IN EARLY TIBET: THE EMERGENCE OF AN IDEOLOGY. Issue 3 (27th February 2018) - Pirie, Fernanda
Abstract: Tibet is distinct within the Buddhist regions of Asia for its claims to have developed religious laws. The rulers of its early empire civilized their people by creating laws on the basis of Buddhist principles—or so it is claimed by the writers of Tibetan historical narratives. In fact, the earliest Tibetan laws were not linked in any significant way with Buddhist principles, even after the religion had been firmly established in the region. In this article I explore why and how the idea of Buddhist law first emerged, examining its development through a number of texts from the empire (sixth to ninth centuries) and the immediate postimperial period (tenth to twelfth centuries). It turns out that more ideological accounts of Buddhist law were developed only as the structures of the empire were collapsing. Nevertheless, they do seem to have resonated with at least one, tenth-century ruler. These narratives set the scene for a long series of historical accounts in which the idea that Tibetan law was based on Buddhist principles took hold—an idea that was maintained well into the twentieth century.